Amino Acid Metabolism - Newsholme, Philip; Stenson, L.; Sulvucci, M.; Sumayao, R.; Krause, M. (Elsevier, 2011)
Proteins exert essential functions in biology, from structural roles, secreted signaling molecules, ion channels, transport, or catalysts of biochemical reactions (enzymes). The unique characteristics of a protein are dictated by its linear sequence of amino acids, termed its primary structure. This sequence can determine the final conformation of a protein and also its interactions with other proteins or molecules to exert their function inside and outside the cells. It is generally accepted that only 20 proteinogenic amino acids are included in the genetic code and therefore regularly found in proteins. However, it is now accepted that a 21st amino acid, selenocyteine, exists in mammalian proteins. Hence, every mammalian protein is constructed from a set of 21 amino acids [4]. Beyond their importance for the synthesis of proteins, amino acids can also be fully or partially oxidized in order to produce energy or to be converted into other compounds such as glucose, fatty acids, ketone bodies, and purine and pyrimidine bases (used for nucleotide synthesis from which RNA and DNA are formed). In this article, we describe the structure, the characteristics, and the metabolism of the key amino acids, and also discuss the importance of their availability in health and disease conditions.